Pengaruh Pemberian Pupuk Kompos Kotoran Sapi Pada Media Tanam Tanah Ultisol Terhadap Pertumbuhan Bibit Pinang Betara (Areca catechu L. var.Betara) Di Polibag - Nasamsir Nasamsir; Ridawati Marpaung; Hayata Hayata; Fani Agustin (Universitas Batanghari, 2023)
Ultisol soils have several constraints, both physical and chemical properties of the soil such as acid to very acidic soil reactions, low to very low organic C, low total N, macronutrients such as low P, K, Ca and Mg, high Al saturation which are toxic to plants, cation exchange capacity (CEC) and base saturation (BS) are low to very low so that they can cause stunted plant growth. This study aims to examine the effect of cow dung compost on Ultisol soil planting media on the growth of Betara betel nut in polybags. This research will be carried out on campus II of Batanghari University Jambi (Pijoan) and soil analysis will be carried out at the Laboratory of the Environmental Service of Jambi Province, this research was carried out for 3 months from April to June 2022. The design used in this study was a completely randomized design (CRD). ) by one factor. The treatment that was tried was cow dung compost (k) with 4 levels of dosage as follows: k0, k1, k2 and k3. Parameters observed included plant height, seedling diameter, plant dry weight, root dry weight and soil chemical properties. To determine the effect of the treatment being tested, the data were analyzed using analysis of variance, then if the analysis of variance showed a significant difference, it was continued with the DNMRT test at a level of 5%. The results showed that the application of cow dung compost had a significantly different effect on plant height, stem diameter, plant dry weight and root dry weight of Betara betel nut. The highest betel nut plant height was found in k3 treatment of 87.41cm and there was an increase in plant height of 54.95% when compared to k0. The highest stem diameter growth was obtained from k3 of 1.17 mm, an increase of 67.14% compared to k0 treatment. The highest plant crown dry weight was obtained in the k3 treatment of 96.72 g and there was an increase of 202.72% compared to k0. The highest root dry weight was obtained in the k3 treatment of 41.02 g and there was an increase of 144.60% compared to k0.